The Role of Principal Leadership in Improving the Quality of Education in Schools based on Independent Curriculum - Mundori Mundori; Denny Denmar; Akhmad Habibi (Universitas Muhammadiyah Enrekang, 2024)
This study aims to explain the understanding of the role of principal leadership in improving the quality of curriculum-based education. The design that will be used in this study is qualitative research. This qualitative description method is a research method that describes, describes, and analyzes objects from a particular situation from all data obtained during field activities. Document interviews and observations are the techniques used in this study. In this study, it reviews the role of principal leadership in improving the quality of education in schools based on the independent curriculum at SMP IT An-Nahl. The application of this design is achieved by collecting data, processing data, and then presenting data with useful information that is easy for readers to understand. In this study using a case study approach, the case is the role of principal leadership in improving the quality of education in schools based on the independent curriculum at SMP IT An-Nahl. In the process of determining this informant, the researcher prefers people who really understand and understand the problem being studied, namely by using purposive sampling naturalistic orientation.